Papel do córtex parietal posterior na geração de drift proprioceptivo em tarefa de apontamento na privação visual - Joao Roberto Ventura de Oliveira (2016)
Proprioceptive drift is the phenomenon related to a greater spatial error magnitude. It is considered as central representation degradation in the visual deprivation. Relation between cortical area of sensorial integration, posterior parietal cortex (PPC), and limited maintenance of working memory is stablished. However, little is known about the association of proprioceptive drift and aiming tasks in visual deprivation. It has been hypothesized that the inhibition of PPC through transcranial direct current stimulation (tDCS) increase the spatial errors in visually deprivated aiming movement and would affect the online control. This study aimed to verify the role of PPC in the proprioceptive drift generation in visually deprivated aiming task. The sample was composed of 24 volunteers, right-handed, from both sexes, aged 18 to 35 years old. A manual aiming task was used in two conditions, with and without vision. For each condition 30 trials were performed. The subjects were distributed in two groups: one that received inhibition of PPC via cathodal tDCS (CG) and placebo group (PG). Application of tDCS occurred during both with and without visual information conditions. Two-way Anovas with repeated measures in second factor were used (2 groups x 2 conditions) to dependent variables: reaction time (RT), movement time (MT), radial error (RE), amplitude (AMP), peak velocity (PV), relative time to peak velocity (RTPV), and number of corrections in the 2° submovement (NC). Results indicated increased RE to CG compared to PG, within visual deprivation condition. Decreased PV and inaltered NC were found for CG compared to PG, in the visual deprivation condition too. Thus, association between PPC and proprioceptive drift hypothesis and spatial proprioceptive drift magnitude increase through PPC inhibition hypothesis were confirmed by significant difference in RE. PPC inhibition affects online control hypothesis is not confirmed, indicated by decreased PV and unaltered NC for CG. Two complementary explanatory hypotheses may relate the alterations in control mechanisms to PPC role in proprioceptive drift appearance, therefore a proprioceptive fading in visual deprivation, impacting in formed representation quality, and a movement errors accumulation by inserting of incorrect information during visual deprivation.